Accountants in Residency Program. - Haseman, Wilber C. (The Accounting Review, 1968)
Abstract A graduate seminar conducted by several prominent accountants invited from industry, government, and public accounting has proved to be a worthwhile addition to the curricula at the University of Missouri, Columbia, Missouri. Time is also allotted for private student consultations. Students participate in the course by responding to and questioning the discussion leader, by summarizing the informal discussions for publication and by writing technical papers on related topics. Development of abilities to recognize; define, and analyze current accounting problems is an important part of any graduate program in accounting. The ability to write clearly, logically and forcibly comes mainly from disciplined practice under the guidance of a critical audience. While many courses in the accounting curriculum may offer the opportunity to practice writing, all too few provide critical guidance to point the way for improvement. The success of the program depends to a large degree upon the calibre of the guest speakers and the novelty and significance of the message they have to deliver.